Rios intermitentes do semiárido brasileiro: o efeito do ambiente e do espaço na estrutura da metacomunidade de peixes - Teixeira, Francisco Keilo (2023)
Intermittent rivers and ephemeral streams represent over half the global stream network and are present on all continents. In Brazil, these rivers are predominant in the semiarid region dominated by the Caatinga, although they are present on a smaller scale in all Brazilian biomes. The ecology of intermittent rivers has progressed significantly in the last two decades, but protection policies are still flawed, leading these rivers to be among the most threatened biodiversity hotspots in the world. The formation of patches of habitats during the natural cycles of drought and flood make them natural laboratories for studying metacommunity ecology. The ecology of metacommunities has progressed a lot in recent decades, but studies on the analysis of the temporal dynamics of metacommunities are incipient. The spatial and temporal dynamics of metacommunities and their generating mechanisms in intermittent rivers remain little explored. Understanding the spatial and temporal variation of metacommunity structure patterns in highly dynamic systems (e.g., intermittent rivers) broadens our understanding of species response to environmental gradients, making it possible to identify the mechanisms and processes underlying the assembly of these metacommunities. In view of the above, we divided this thesis into two chapters: in chapter I we reviewed intermittent rivers and ephemeral streams and discussed the global distribution, flow patterns, ecology and conservation policies emphasizing the rivers of the Brazilian semiarid region, in chapter II we combined the Metacommunity Structure Elements (EEM) and partitioning of variance (pRDA) approach, to identify the relationships between the effects of environment and space on the structure of fish metacommunities. We found three types of metacommunity structures (nested, random and quasi-nested) along of the dry, wet and re-wetting phases. We observed that environmental factors (e.g., volume, temperature, dissolved oxygen, pH and mesohabitat diversity) are preponderant in determining the metacommunity structure of fish. The nested structures are best-fit structure during the dry phase, while the random distribution is more common in the dry and wet phases of the rivers. Our results suggest that the structure of the fish metacommunity was better explained, respectively, by environmental and spatial factors during the dry and wet of the river. The results obtained by the NODF method (Nestedness metric based on Overlap and Decreasing fill) confirm the strong temporal nesting of fish metacommunities in different phases of the river hydrological cycle.